PERBEDAAN RIWAYAT PENYAKIT TIROID TERDAHULU, METASTASIS DAN ABNORMALITAS PEMERIKSAAN ULTRASONOGRAFI ANTARA PASIEN KARSINOMA TIROID PAPILER KLASIK DAN VARIAN FOLIKULER DI RSUP Dr. KARIADI SEMARANG - Firdauzi Putri, Nabila Zenska; Istiadi, Hermawan; Wikanta, Edmond Rukmana; Miranti, Ika Pawitra (RSUP Dr. Kariadi, 2021)
Background: Papillary thyroid carcinoma (PTC) is the most common carcinoma, accounting for more than 90% of all malignancies, where the most variants are classic papillary thyroid carcinoma and follicular variant papillary thyroid carcinoma (PTCVF). The characteristics of previous thyroid disease history, regional metastases, and ultrasound examination results can influence the clinical examination between the two variants of PTC, namely classic PTC and PTCVF. Aim: Understanding the differences in the history of previous thyroid disease, metastases, and ultrasound examination abnormalities between Classical Papillary Carcinoma and Follicular variants at Dr. Kariadi Hospital, Semarang. Methods: A cross sectional study with consecutive sampling method in classic PTC and PTCVF patients in Dr. Kariadi Hospital, Semarang who was diagnosed in the period January to June 2019. In this study, the number of samples obtained was 18 medical records with classic PTC cases and 20 medical records with PTCVF cases. The dependent variables, namely history of previous thyroid disease, regional metastases, and ultrasound examination abnormalities, all of which were on an ordinal scale, were analyzed using non-parametric chi-square test and Fisher's Exact test. Results: In the non-parametric chi-square test and Fisher's Exact test, the results were not significant (p = 0.474), regional metastases were not significant (p = 0.359), ultrasound size abnormalities were not significant (p = 0.323), and abnormalities. ultrasound nodal was not significant (p = 0.595). Conclusion: There was no statistically significant difference in the history of previous thyroid disease, regional metastases, and ultrasound examination abnormalities between classic PTC and PTCVF patients at Dr. Kariadi Hospital, Semarang.